Immune Thrombocytopenia in a Child with T Cell Lymphoblastic Lymphoma - Kayo Tokeji; Sachi Sakaguchi; Tomoko Kurimoto; Junya Fujimura; Toshiaki Shimizu (Case Reports in Hematology)
We describe the case of a 13-year-old boy who presented with persistent thrombocytopenia during maintenance chemotherapy with mercaptopurine and methotrexate for T cell lymphoblastic lymphoma. He was diagnosed with immune thrombocytopenia (ITP) after thorough investigations for the relapse of lymphoma and was successfully treated with immunoglobulin and steroids. ITP is known to be associated with chronic lymphocytic leukemia, Hodgkin lymphoma, and various types of non-Hodgkin lymphoma but rarely with T cell non-Hodgkin lymphoma or in children. Diagnosis of ITP with lymphoma is challenging due to the many factors affecting platelet counts, and ITP often complicates the diagnosis or treatment course of lymphoma. The underlying mechanism of ITP with NHL is still unclear. Drug-induced immunomodulation with a reduction of regulatory T cells might have contributed to the development of ITP in our case.